New treatment options in bone metastases patients - Pawlicki, Marek (Contemporary Oncology/Współczesna Onkologia, 2002)
Changes in the therapeutic strategies of bone metastases comprise novel surgical techniques, partially radiotherapy and new generations of biphosphonates. Surgical treatment is thought to be a basic therapy in certain patients with bone metastases. Biphosphonates have been recently demonstrated to significantly improve survival of patients with some types of cancer e.g. breast cancer and are supposed to be a crucial adjuvant treatment supplementing basic therapy (surgery, radiotherapy). Although radiotherapy has not been shown to improve survival of patients with bone metastases it significantly improves the quality of their life. Quite often it is reasonable to support the sophisticated clinical therapies with some other kinds of treatment such as physical rehabilitation. Combination of different cancer treatment strategies may not only improve survival of patients (10-40%), but also reduce the total costs of therapy mostly by decreasing the number of patients requiring long-term hospitalization.